Elimination of nuclear war threat is the Precondition of Abolition of Nuclear Weapons - Ryol, Kang Mun (Mongolian Journal of International Affairs, 2011)
DOI: 10.5564/mjia.v0i14.26 Mongolian Journal of International Affairs No.14 2007 pp.68-70